Indonesia - Fariz, Ferdinan; Permana, Ilyas; Hidayatuloh, Fikri; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
Zakat has a strategic role in realizing social justice and poverty alleviation, but its distribution practices in Indonesia still face various obstacles such as low transparency, weak management of amil institutions, and the dominance of consumptive patterns that have less long-term impact. This research aims to analyze the urgency of reorienting the direction and pattern of zakat distribution to be more effective in improving the welfare of the people. The method used is library research by reviewing the literature, regulations, and relevant results of previous research. The results of the study show that the distribution of zakat needs to be directed from traditional consumptive patterns to productive patterns that are able to empower mustahik to become new muzakki. This reorientation emphasizes the importance of transparency, program innovation, professionalization of amil, and synergy between the government and the community in the management of zakat. In conclusion, the reorientation of zakat distribution is a strategic step to optimize the economic function of zakat in reducing social disparities and strengthening equitable development in Indonesia.